Perspective: Cancer Patient Management Challenges During the COVID-19 Pandemic - Terracciano, Daniela; Buonerba, Carlo; Scafuri, Luca; De Berardinis, Piergiuseppe; Calin, George A.; Ferrajoli, Alessandra; Fabbri, Muller; Cimmino, Amelia (Frontiers in Oncology, 2020)
On March 11, 2020 the WHO has declared the Coronavirus disease 2019 (COVID-19) a global pandemic. As the last few months have profoundly changed the delivery of healthcare in the world, we should recognize the effort of numerous comprehensive cancer centers to share experiences and knowledge to develop best practices to care for oncological patients during the COVID-19 pandemic. Patients as well as physicians must be aware of all these constraints and profound social, personal, and medical challenges posed by the tackling of this deadly disease in everyday life, in order to adjust to such a completely novel scenario.This review will discuss the facing challenges and the current approaches that cancer centers in Italy and Usa are adopting in order to cope with clinical and reserach activities .